2017
DOI: 10.1097/md.0000000000006866
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer

Abstract: The aim of this study was to evaluate the short-term test-retest reproducibility of diffusion-weighted magnetic resonance imaging (DW-MRI) parameters of rectal cancer with 3.0T MRI.Twenty-six patients with rectal cancer underwent MRI, including diffusion-weighted imaging with 8 b values. Apparent diffusion coefficient (ADC) and intravoxel incoherent motion (IVIM) parameters (D, pure diffusion; f, perfusion fraction; D∗, pseudodiffusion coefficient) were, respectively, calculated. The short-term test-retest rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Therefore, the results of the D* and f values may be related to the location of the lesion and the feeding artery. Furthermore, previous studies have reported that the D* and f values are not accurate in the assessment of the tumor differentiation grades because of their intrinsic instability, poor reproducibility, and lower diagnostic efficiency[ 33 , 34 ]. Nevertheless, Vincenza Granata et al[ 18 ] demonstrated that the f values were significantly different in the HCC groups with G1, G2, and G3 histological grades, and a significant correlation was reported between the f value and the histologic grade, which is in disagreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results of the D* and f values may be related to the location of the lesion and the feeding artery. Furthermore, previous studies have reported that the D* and f values are not accurate in the assessment of the tumor differentiation grades because of their intrinsic instability, poor reproducibility, and lower diagnostic efficiency[ 33 , 34 ]. Nevertheless, Vincenza Granata et al[ 18 ] demonstrated that the f values were significantly different in the HCC groups with G1, G2, and G3 histological grades, and a significant correlation was reported between the f value and the histologic grade, which is in disagreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Some encouraging first results have been shown for IVIM in rectal cancer to predict response, 60,61,71 for differentiating between metastatic (N+) and non-metastatic (N-) lymph nodes, 119 and to predict prognostic markers such as TNM-stage, 102,113 tumour differentiation grade, 102 lymphovascular invasion, 108 microvessel density 113 and KRAS status. 114 Potential drawbacks of the IVIM method are its test-retest reproducibility 120 and that measurements may be significantly influenced by scan parameters such as the echo time. 121 There is currently no consensus on how IVIM analysis should best be performed, as is also illustrated by the different imaging protocols used in the current literature.…”
Section: Intravoxel Incoherent Motionmentioning
confidence: 99%
“…MRI demonstrates high tissue resolution, which can clearly show the penetration depth of the tumor on the rectal wall and the connection between the surrounding soft tissue and the tumor [17]. Sun et al [18] studied the accuracy of high-field 3.0T-MRI in the diagnosis of rectal cancer and found that it had 100% sensitivity and 67% specificity in diagnosing muscularis propria invasion; that it had 91% sensitivity and 93% specificity in diagnosing surrounding tissue invasion; and that it had 64% sensitivity and 92% specificity in diagnosing lymph node metastasis. Zhang et al [19] studied the accuracy of MRI in the circumferential margin detection before and after NCRT and found that the accuracy decreased after NCRT.…”
Section: Discussionmentioning
confidence: 99%